A PHENOMENOLOGY OF FINANCIAL REPORT OF POLITICAL PARTIES IN BANTEN PROVINCE - Simanjuntak, Dahnil Anzar (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2016)
Political Parties propose their politician to the society for voted. They produce decision maker in legislative in particular. They had significant role in budgeting activities for public interest. Thus, transparency and accountability are absolutely needed, and the instrument of them, only couldprovide by accountancy. Political actor has significant role for made parties financial statement, based on those understanding, these research used phenomenology method, for answer how financial report made by political parties via their politicians, and what about with their perspectives about accountability and transparency. Transparency and accountability not as major goal for political parties. Political Parties in the it was clearly, the reason for made financial statement was not cause effort for creating public transparency and accountability in Banten Province, but more as reason for avoided from punishment, refer to the KPU Rule. This research reveal, political parties of financial statement made on as formality without substances for presenting accountability andtransparency, there was found a conclusion that political parties in Banten Province have a very low rates of accountability and transparency.